"Brighter the moon over my home village": Some patterned ways of speaking about home among rural–urban migrant workers in China. Issue 1 (2nd January 2016) - Li, Meng
ABSTRACT: Drawing on a social constructionist approach and Philipsen's theoretical framework of cultural communication, this study examines how rural–urban migrant workers in China construct the meaning of home in their communication about migration. Interviews with migrant workers and participant observation of their everyday conversations reveal that migrant workers frequently evoke a cultural code of home attachment and actively construct a political code of displacement to construe their prolonged liminality between the city and the countryside. Implications for studying the use of culturally specific and politically situated discursive practices to address common challenges of displacement are discussed.